Precarious Crossings Immigration, Neoliberalism, and the Atlantic - Perisic, Alexandra (The Ohio State University Press, 2019)
Examines the underlying precarity in twenty-first-century immigrant fiction and reveals the contradictions inherent in neoliberalism as an ideology.